2016
DOI: 10.1111/ejss.12387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil fertility and soil biodiversity with dsDNA as a covariate in a regression estimator for mean microbial biomass C

Abstract: The analytical determination of microbial biomass carbon is time‐consuming, which limits its use as a reference biochemical property for characterizing soil fertility and soil biodiversity of soil mapping units (SMUs). This paper explores whether the efficiency of sampling strategies for estimating the means of microbial biomass C (MBC) of SMUs can be increased with dsDNA as an ancillary variable in a regression estimator, leading to a model‐assisted sampling strategy. The map unit means of dsDNA are unknown; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Not less important, co-extraction of humic substances was much lower compared to traditional procedures and extraction time was very low. Enzymes can be efficiently desorbed by heteromolecular exchange with a bead-beating procedure [ 54 ] that improves the extraction yields and greatly shortens the extraction time as shown also for dsDNA quantitation [ 56 ] as soil microbial biomass indicator [ 57 ]. Ferrarini et al showed that the assay can be performed on 384-well microplates using fluorogenic substrates and a number of enzymes (>20) can be assayed by using the same soil extract [ 47 ].…”
Section: Using-omics To Assess Soil Microbial Diversitymentioning
confidence: 99%
“…Not less important, co-extraction of humic substances was much lower compared to traditional procedures and extraction time was very low. Enzymes can be efficiently desorbed by heteromolecular exchange with a bead-beating procedure [ 54 ] that improves the extraction yields and greatly shortens the extraction time as shown also for dsDNA quantitation [ 56 ] as soil microbial biomass indicator [ 57 ]. Ferrarini et al showed that the assay can be performed on 384-well microplates using fluorogenic substrates and a number of enzymes (>20) can be assayed by using the same soil extract [ 47 ].…”
Section: Using-omics To Assess Soil Microbial Diversitymentioning
confidence: 99%
“…Soil microbial biomass was determined as double-strand DNA (dsDNA) content (Bragato et al, 2016) in 300-mg DW soil samples through DNA extraction with a 0.12 M, pH 8 Na 2 HPO 4 buffer using bead beating and quantification with PicoGreen reagent, as described by Fornasier et al (2014). Biomass was expressed as µg dsDNA g -1 soil D. W.…”
Section: Rhizosphere Microbial Biomass and Enzymatic Activitymentioning
confidence: 99%
“…All measurements were taken in triplicate and the activities were expressed as nanomoles of 4‐methylumbelliferone (MUF) (or 7‐amino‐4methyl coumarine [AMC]) g −1 dry soil h −1 . MB was determined using the double‐stranded DNA (dsDNA) content as a proxy (Bragato et al., 2016). DNA was extracted as described by (Fornasier et al., 2014).…”
Section: Methodsmentioning
confidence: 99%